KORUPSI DAN MONEY LAUNDERING (Studi Kasus Indonesia Dan Korea Selatan merusak sistem sosial dan keuangan global) - M Zaki Suaidi (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2021)
Corruption in Indonesia and in other countries has become a latent problem and is very difficult to eradicate. Various attempts have been made to eradicate this corruption: both at the country level itself and at the international level. In general, the eradication of corruption is carried out through the establishment of a corruption eradication agency or institution which is legalized through a law. Furthermore, the following presentation is a case study of Indonesia and South Korea on how to eradicate corruption. The practice of money laundering has often involved cross-border transactions, because by conducting such transactions between countries, it is very effective in eliminating traces of illegal flows of funds. With the increasing globalization of the international financial system, money laundering, as a criminal activity, is becoming more and more common, but in turn it greatly affects and damages the global social and financial system. In summary, it can be concluded that in the era of globalization the problem of corruption and money laundering is becoming increasingly widespread because the existence of this crime involves many factors that cross national boundaries. The problem of corruption and money laundering is the dark side of globalization. Handling corruption and money laundering cannot be resolved quickly and easily, but it takes time, commitment, political will, and support from all parties: national government, society, and multilateral cooperation. Learning from South Korea, Indonesia and the international community, for example, requires a more efficient structure-based bureaucratic reform by upholding the spirit of 'Good Governance' and 'Check and Balance' which is expected to encourage all elements of the nation to work together to solve corruption at a practical level.